FIRST LESSONS IN DEMONSTRATIVE GEOMETRY - Newell, M. J.; Harper, G. A. (The Mathematics teacher, 1921)
It is considered good pedagogy to make the approach to any new subject by means of related subjects of more elementary character. The first few lessons in Geometry need furnish no exception to the above rule. From his work in mensurational arithmetic, the pupil has a fair conception of areas of rectangles triangles and circles, and volumes of some of the solids. From his experiences in everyday life, he has some idea of the fundamental meaning of the terms: point, straight line, angle, right angle, etc. From Algebra he has acquired the ability to choose symbols wisely and to use them skilfully, and has discovered how valuable they are in shortening operations. All of this fund of information may be used to great advantage by the careful teacher in the introductory lessons of Geometry.